Gold Nanostructures: Synthesis and Applications for Cancer Therapy - ชมภูสอ, อภิวัฒน์ (KKU Science Journal, 2013)
Gold nanostructures have been used in a broad range of biological and biomedical applications due to their brilliant optical properties. This review provides the synthesis of gold nanostructures for examples nanospheres, nanorods, nanoshells, and nanocages. By engineering the size, shape and structure of gold, the surface plasmon resonance can be tailored from the visible to the near infrared region. In the second part, cancer therapies that take benefit of the radiative properties resulting from surface plasmon oscillation are presented. Tunable optical properties coupled with the inertness of gold make them an excellent platform for biomedical applications.